Investigating the Anti-Inflammatory Effects of RCI001 for Treating Ocular Surface Diseases: Insight Into the Mechanism of Action - Kim, Seunghoon; Jang, Ye Won; Ku, Young-ah; Shin, Yungyeong; Rahman, Md Mahbubur; Chung, Myung-Hee; Kim, Yong Ho; Kim, Dong Hyun (Frontiers in Immunology, 2022)
The ocular surface is continuously exposed to external environmental factors, and innate and adaptive immunity play crucial roles in ocular surface diseases (OSDs). Previously, we have reported that the topical application of RCI001 affords excellent anti-inflammatory and antioxidant effects in dry eye disease and ocular chemical burn models. In the present study, we examined the inhibitory effects of RCI001 on the Rac1 and NLRP3 inflammasomes in vitro and in vivo. Following RCI001 application to RAW264.7 and Swiss 3T3 cells, we measured Rac1 activity using a glutathione-S-transferase (GST) pull-down assay and G-protein activation assay kit. In addition, we quantified the expression of inflammatory cytokines (interleukin [IL]-1β, IL-6, and tumor necrosis factor [TNF]-α) in lipopolysaccharide (LPS)-stimulated RAW264.7 cells using ELISA and real-time PCR. In the mouse ocular alkali burn model, RCI001 was administered via eye drops (10 mg/mL, twice daily) for 5 days, and 1% prednisolone acetate (PDE) ophthalmic suspension was used as a positive control. Corneal epithelial integrity (on days 0-5) and histological examinations were performed, and transcript and protein levels of Rac1, NLRP3, caspase-1, and IL-1β were quantified using real-time PCR and western blotting in corneal tissues collected on days 3 and 5. We observed that RCI001 dose-dependently inhibited Rac1 activity and various inflammatory cytokines in LPS-stimulated murine macrophages. Furthermore, RCI001 restored corneal epithelial integrity more rapidly than corticosteroid treatment in chemically injured corneas. Compared to the saline group, activation of Rac1 and the NLRP3 inflammasome/IL-1β axis was suppressed in the RCI001 group, especially during the early phase of the ocular alkali burn model. Topical RCI001 suppressed the expression of activated Rac1 and inflammatory cytokines in vitro and rapidly restored the injured cornea by inhibiting activation of Rac1 and the NLRP inflammasome/ IL-1β axis in vivo. Accordingly, RCI001 could be a promising therapeutic agent for treating OSDs.